Constructing gender and sexuality in a teachers' guide of health education - Suviranta, Ilona (2020)
This study aims to find out how gender and sexuality are constructed in a teachers’ guide of health education. Sexuality and gender complex and interconnected concepts that intersect with power, race, and class as well. The rights of gender and sexual minorities have been widely discussed in recent years. At schools, LGBTQ youth still experiences more bullying and harassment than their heterosexual/cisgender peers. Research suggests that when sexuality and gender are discussed at school, LGBTQ students feel more safe and comfortable in their educational environments, which is why it is important to study LGBTQ representations. Critical discourse analysis and queer linguistics are used in this study to understand the underlying ideologies and power relations better, and to focus on the queer point of view. The study aims to understand how much the constructions of gender and sexuality relies on cisnormativity and heteronormativity. Special attention is given to the construction of dichotomies, as they support heteronormativity and cisnormativity and further marginalise sexual and gender minorities. The data of the study consists of the sex and relationship education -part of a teachers’ guide of health education, as it is most relevant to the topics of gender and sexuality. The guide was published in 2009. The analysis is built around the varying discourses in the data to better understand the different contexts that LGBTQ issues are talked about. The research questions are: 1. How are gender and sexuality constructed in the data? 2. What are the discourses that construct gender and sexuality in the data? The construction of sexuality differs from the construction of gender. Sexuality is constructed through varying discourses: fluid sexuality, sexuality as a personal trait, sexuality as sexual rights, sexuality as relationships and sexuality as sexual acts. Sexuality is portrayed as a fluid and personal attribute that can enrich one’s life. Gender, however, is only constructed as a dichotomy, and is given no definitions, thus portraying it as “common sense” knowledge.